Analisis Keterampilan Metakognitif Mahasiswa dalam Mengkaji Implementasi Kurikulum Kimia di SMA melalui Project Based Learning - Harta, Johnsen (Jurnal Riset Pendidikan Kimia (JRPK), 2019)
The existence of the curriculum not only emphasizes the importance of attention to education, but also our efforts to explore and interpret the vital role of curriculum that will bring Indonesian education to international level. Especially in chemistry learning, prioritizing the structure and implementation of the right curriculum is an essential part of introducing and reviving the role of meaningful chemical learning. This study aims to investigate the metacognitive aspects of students in reviewing the implementation of senior high school in Yogyakarta. This research is a quantitative-qualitative descriptive study with 3 project based learning. The research was conducted from August to December 2018. The research instruments used were interview sheets, test questions according to metacognitive level indicators, questionnaires in the form of Metacognitive Awareness Inventory (MAI), presentation-discussion assessment sheets, and reflection sheets. Data collection techniques include descriptive analysis of the results of metacognitive level tests, MAI questionnaire analysis using Rasch Model, analysis of interviews, observation, and reflection descriptively. The results show that students were good at analyzing curriculum structure and studying the implementation of high school and vocational chemistry curriculums in Yogyakarta with the acquisition of an average score of 82.65 for curriculum comprehension, component surgery and high school chemistry content in the curriculum having an average score of 89.57. Regarding the final value of the group project, the average value of the ability and analysis aspects in the chemistry teachers interview is 87.11; the average value for presentation design is 91.51; and the average value of presentation and discussion skills is 83.14. In the metacognitive test, 87.5% and 97.14% of students were completed and supported by Cronbach's Alpha Value of 0.94 for the results of the MAI questionnaire analysis using the Rasch Model. The five metacognitive levels have been achieved well. Keywords Project based Learning, Metacognitive Skills, Curriculum Implementation, Chemistry at Senior High School